Vulvar Fibroadenoma with Lactational Changes in Ectopic Breast Tissue - Naama Lev-Cohain; Payal Kapur; Ivan Pedrosa (Hindawi Limited, 2013)
Ectopic breast tissue represents any type of breast tissue found outside its normal location in the pectoral region. The second most common location for ectopic breast tissue after axilla is the vulvar region. We present a case of a healthy 20-year-old female, G1P1, who presented to the Emergency Department with a sudden increase in size of a painful mass located in her vulva, which started 4 days after a spontaneous vaginal delivery and 3 days after initiation of breast-feeding of her newborn. She reported a stable, smaller, painless mass in the same location for almost 2 years prior to this episode. After surgical excision, a fibroadenoma with lactation changes within ectopic breast tissue was confirmed.